An analysis of teachers’ instructions and feedback at a contemporary dance university - Soerel, Benjamin F.; Plaatsman, Larissa A.; Kegelaers, Jolan; Stubbe, Janine H.; van Rijn, Rogier M.; Oudejans, Raôul R. D. (Frontiers in Psychology, 2023)
Abstract Background: Given the demands posed by excessive practice quantities in modern dance, physical and mental health can be compromised. Therefore, there is a need to consider how quality of practice may be improved and possibly even reduce training times. Sports literature has shown that instructions and feedback given by coaches can have an effect on the quality of training and influence self-regulation and the performance of athletes. However, currently little is known about the use of instructions and feedback by dance teachers. The aim of the current study was, therefore, to examine the type of instructions and feedback given by dance teachers during various dance classes. Methods: A total of six dance teachers participated in this study. Video and audio recordings were made of six dance classes and two rehearsals at a contemporary dance university. The dance teacher’s coaching behavior was analyzed using the modified Coach Analysis and Intervention System (CAIS). Additionally, feedback and instructions were also examined in terms of their corresponding focus of attention. Absolute numbers, as well as times per minute (TPM) rates were calculated for each behavior before, during, and after an exercise. Absolute numbers were also used to calculate ratios of positive-negative feedback and open-closed questions. Results: Most feedback comments were given after an exercise (472 out of 986 total observed behaviors). Improvisation had the highest positive-negative feedback ratio (29) and open-closed questions ratio (1.56). Out of the focus of attention comments, internal focus of attention comments were used most frequently (572 out of 900). Discussion/conclusion: The results make clear that there is a large variability in instructions and feedback over teachers and classes. Overall, there is room for improvement towards a higher positive-negative feedback ratio, a higher open-closed question ratio and producing more comments eliciting an external focus of attention.